Diet-microbiome-gut-brain nexus in acute and chronic brain injury - Krakovski, Maria Alexander; Arora, Niraj; Jain, Shalini; Glover, Jennifer; Dombrowski, Keith; Hernandez, Beverly; Yadav, Hariom; Sarma, Anand Karthik (Frontiers in Neuroscience, 2022)
In recent years, appreciation for the gut microbiome and its relationship to human health has emerged as a facilitator of maintaining healthy physiology and a contributor to numerous human diseases. The contribution of the microbiome in modulating the gut-brain axis has gained significant attention in recent years, extensively studied in chronic brain injuries such as Epilepsy and Alzheimer's Disease. However, there is growing evidence that gut microbiome also contributes to acute brain injuries like stroke(s) and traumatic brain injury. Microbiome-gut-brain communications are bidirectional and involve metabolite production and modulation of immune and neuronal functions. The microbiome plays two distinct roles: it beneficially modulates immune system and neuronal functions; however, abnormalities in the host’s microbiome also exacerbates neuronal damage or delays the recovery from acute injuries. After brain injury, several inflammatory changes, such as the necrosis and apoptosis of neuronal tissue, propagates downward inflammatory signals to disrupt the microbiome homeostasis; however, microbiome dysbiosis impacts the upward signaling to the brain and interferes with recovery in neuronal functions and brain health. Diet is a superlative modulator of microbiome and is known to impact the gut-brain axis, including its influence on acute and neuronal injuries. In this review, we discussed the differential microbiome changes in both acute and chronic brain injuries, as well as the therapeutic importance of modulation by diets and probiotics. We emphasize the mechanistic studies based on animal models and their translational or clinical relationship by reviewing human studies.